Peningkatan Kualitas Bacaan Kitab Kuning bagi Santri Desa di Pondok Pesantren Wali Songo Pleret Bantul - Muhammad Khabibullah; Ahmad Shofiyuddin Ichsan; Muh. Subhan Ashari (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
This research reveals how to improve reading of ‘the yellow book’ through the sorogan method for village students at Islamic Boarding School Wali Songo Pleret, Bantul and what are the factors and obstacles in the application of the sorogan method to improve reading of ‘the yellow book’ of village students in the pesantren. This research is a qualitative descriptive research, while the data collection techniques used interviews, observation and documentation. The results showed that the ustaz's efforts in improving the ability to read ‘the yellow book’ for village students by applying the sorogan method were considered very effective. This is based on the main purpose of the sorogan method, namely improving reading quality, understanding content, and being able to reveal the content of reading. Not only that, the increase can also be seen from the many supporting factors and the lack of inhibiting factors.